Synthesis and Characterization of Polyaniline, using Different Dopant, for Sensing Application of Pollutant Gases - Deshpande, Naseem; Chakane, Sanjay; Borude, Ranjit R. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Conducting polymers have been attracting considerable attention of researchers worldwide since 1980, due to their unique electrical, optical, thermal and magnetic properties. Among these polymers, polyaniline (PAni) is most popular as it can be synthesized for specific applications like rechargeable batteries, bio-sensors, corrosion paintings, organic electronic materials, EMI shielding, light emitting diodes etc. In this paper, we report synthesis of conducting polyaniline using different dopants such as HCL, HCLO\(_4\), HNO\(_3\) and H\(_2\)SO\(_4\) by oxidative chemical polymerization of aniline. The synthesized polyaniline materials were characterized by Fourier Transform Infra-red Spectroscopy (FTIR), Powder X-Ray Diffraction (XRD), Energy Dispersive X-ray analysis (EDAX) and Ultra-Violate (UV-VIS) Spectroscopy techniques.